Model STEP (Ruang, Tugas, Peralatan, Orang) untuk Meningkatkan Kecerdasan Intrapersonal Siswa Sekolah Dasar - Edwin Nurillah Firdaus; Anggi Setia Lengkana; Muhammad Nur Alif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of the STEP Model (Space, Task, Equipment, People) on the development of intrapersonal intelligence in elementary school students. Intrapersonal intelligence is a core component of character education, encompassing self-awareness, emotional regulation, self-reflection, and metacognition. These aspects are crucial in helping students understand, manage, and direct themselves effectively in both learning and daily life. This research employed a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of 70 third-grade elementary school students, divided proportionally into two groups: the experimental group (n = 35), which received instruction using the STEP Model for twelve weeks, and the control group (n = 35), which followed conventional instruction. The Intrapersonal Intelligence Scale (PKINT) was used as the primary instrument to assess four dimensions: self-awareness, emotional regulation, self-reflection, and metacognition. Data were analyzed using normality and homogeneity tests, followed by an analysis of covariance (ANCOVA). The results indicated that the data were normally distributed and the variance between groups was homogeneous. ANCOVA revealed a significant effect of the STEP Model, with F = 32.18 and Sig. = 0.000 < 0.05. Descriptively, the average score of the experimental group increased from 1.91 (pre-test) to 3.94 (post-test), while the control group showed only a slight increase from 1.89 to 2.12. In conclusion, these findings confirm that the STEP Model substantially enhances self-awareness, emotional regulation, self-reflection, and metacognition. Therefore, the STEP Model can be considered an effective and innovative learning approach that fosters intrapersonal intelligence and supports character education in elementary schools. Keywords: Intrapersonal Intelligence, STEP Model, Character Education, Elementary School